Stress-strain model for concrete confined with CFRP jackets - Turgay, T.; Koksal, H. O.; Polat, Z.; Karakoc, C. (ELSEVIER SCI LTD, 2009)
Enhancement of strength and ductility is the main reason for the extensive use of FRP jackets to provide external confinement to reinforced concrete columns especially in seismic areas. Therefore, numerous researches have been carried out in order to provide a better description of the behavior of FRP-confined concrete for practical design purposes. Most of the existing models are based on the improved or modified forms of the well known empirical formula of Richart et al. derived from the tests on concrete cylinders. Compressive strength of concrete is predicted without a failure criterion for this modeling approach. There exist only a few models that employ the simplified or modified forms of five-parameter failure criterion proposed by William-Warnke. This paper primarily concentrates on the modeling of FRP-confined concrete using a practical failure surface based on only unconfined compressive strength of concrete. A large comparative analysis is accomplished for the existing test data of 127 cylindrical concrete specimens confined with CFRP jackets. The performance of five existing analytical models for the prediction of the compressive strength of FRP-confined concrete is evaluated leading to the detection of the proposed approach as the most accurate one through this comparative study. Moreover, the complete stress-strain curves of eight concrete cylinders obtained from four different experimental studies are plotted adopting both the stress-strain relation of Saenz and the predictions for compressive strength of the approach. Comparisons between the experimental and analytical results point out that the proposed approach provides satisfactory predictions for both the compressive strength and the stress-strain plots of CFRP-confined concrete. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: COMPRESSIVE BEHAVIOR; COMPOSITE JACKETS; FIBER COMPOSITES; COLUMNS; STRENGTH; DUCTILITY; SHEETS; Materials Science